Stretching exercises on the men's professional tennis circuit - Reque, J. (2002)
On the ATP circuit, players use a variety of stretching exercises. Some players choose to stretch on their own, whereas others use the help of physical trainers or physiotherapists. Still others consider stretching unnecessary and perform hardly any stretching exercises at all. To gain more insight into the use of stretching exercises by professional tennis players, a survey was carried out to study the frequency and type of stretching exercises practised by ATP players. During a professional tennis tournament (St. Poelten 2002), the author conducted a survey investigating the frequency and type of stretching exercises performed by pro players on days on which they only had a singles match. Twenty players participated in the study. Results: The following data were obtained: Seventy-five percent of the players performed passive stretching of the lower extremities and of the trunk at least once per day, and 45% twice or more times per day. The upper extremities were stretched less often: 35 % of the players stretched the upper extremities once per day and 28% stretched at least twice per day. All the participants used active stretching daily and 75% of the players used this twice daily. Only 20% used the contraction-relaxation technique. Seventy percent received massages regularly, with 40% of these receiving massages three or more times per week. Thirty-five percent of the players travelled with a personal trainer. All of these players used passive stretching. A minority of the players (10%) used postural stretches. Discussion All players perform active static stretches. However, these are usually performed without proper control or expertise. Furthermore, the same exercises are always performed, with a time interval and variety that are inadequate. Those who do lower extremity stretches also exercise their chest and back. This is most common on the tennis circuit. However, few players perform stretching exercises of their upper extremities. All the players who travel with trainers do passive stretches, including passive stretches of the upper extremities. These are also the only players who use the contraction-relaxation technique. Only half of the players stretch more than twice a day. Other than passive stretches and active static stretches, few players use other stretching techniques. Conclusions and recommendations It is imperative to stress the importance of stretching to tennis players from the start. The best way to convey this message is to include stretching routines for players beginning at a young age, so that they become accustomed to performing these exercises on a regular basis. Passive stretching has been shown to be the best method to improve flexibility and is therefore very important. In order to stretch passively, one needs a physical trainer or the help of another player. It is just as important to stretch the upper extremities, as it is to stretch the trunk and lower extremities. When performing active stretching, it is important to vary the exercises. The ideal programme would be to maintain a routine of 10 to 15 exercises and, sporadically, include new exercises and drop others based upon the requirements of the player. Lastly, it is very important to include methods such as the contraction-relaxation technique and postural exercises in a complete stretching programme.